Il ruolo di Posidonia oceanica nel contrastare gli effetti dell'acidificazione degli oceani sullo sviluppo larvale del riccio di mare Paracentrotus lividus - GIANNESSI, JOANNA (Pisa University, 2022)
Increasing anthropogenic CO2 emissions are driving a range of environmental changes and one of the key concerns is the rapid acceleration of Ocean Acidification (OA) and associated reduction in pH. According to the Special Report on Emissions Scenarios (SRES) of the Intergovernmental Panel on Climate Change (IPCC), the oceans are expected to be progressively more acidic and their pH could decrease by 0.4 units by 2100, going from the current value of about 8.1 to about 7.7. Changes in seawater chemistry could have direct negative effects on calcifying organisms, which could, in turn, have negative ecological, economic and human health impacts. Habitat-forming organisms, such as seagrasses, have an important role in ameliorating stressful conditions and may be a solution to provide refugia from OA for marine organisms. This study aimed to determine if the seagrass Posidonia oceanica benefits the larval development of sea urchin Paracentrotus lividus, and if these benefits can modify any anticipated negative impacts of ocean acidification. Two experiments were carried out: (i) evaluation of larval development in terms of growth anomalies and larval malformations after 72 hours from fertilization and (ii) evaluation of morphometric larval development after 30 days. The pH values used were those expected by the IPCC ‘high emission scenario’ (RCP8.5), which assumes a continuous decrease in the ocean surface pH until it reaches values of approximately 7.7 by 2100. In this regard, future and ambient ocean acidification conditions were simulated in 500 L mesocosms at control (~8.1) and low (~7.7) pH, with and without P. oceanica. For the first experiment, the percentage of regularly developed and malformed larvae was evaluated. In the second experiment, larval size such as length and width were measured. Results showed that seagrass P. oceanica was beneficial for larval development at low pH (~7.7), contributing to a better larval development of P. lividus both in terms of growth and morphology after 72h and in terms of ...